HUBUNGAN DURASI MENDERITA HIPERTENSI DENGAN KEJADIAN RETINOPATI HIPERTENSI DI RSUD DR. A. DADI TJOKRODIPO BANDAR LAMPUNG PERIODE 2017-2020 - Jyoti Krisna Murti; Rani Himayani; Hanna Mutiara; Muhammad Yusran (Majority, 2023)
Hypertension in Indonesia increase every year until in 2018 reached 34.1%. Long duration hypertension cause organ damage, hypertensive retinopathy is one of them. Hypertensive retinopathy shows changes in retinal vascularity such as narrowing and sclerosis in response to increased pressure of blood. The purpose of this study was to determine the relationship between the duration of hypertension and event of hypertensive retinopathy in RSUD Dr. A. Dadi Tjokrodipo Bandar Lampung Period 2017-2020. This study used an observational analysis research method with a cross sectional approach. The research subjects consisted of 168 samples. Sampling method using total sampling. Data on the duration of hypertension and the event of hypertensive retinopathy were taken from medical records. The analytical test used is the chi-square test. This study that of the 168 respondents with hypertension, 53.0% were aged 40-60 years. Patients with hypertension are male as much as 65.5%. Patients with hypertension degree 2 as much as 71%. Based on the duration of suffering from hypertension, the most common duration was 61.3%. As many as 72.6% of hypertensive patients did not experience hypertensive retinopathy, while 27.4% had hypertensive retinopathy. The results of chi-Square analysis showed that there was a significant relationship between the duration of suffering from hypertension and the incidence of hypertensive retinopathy (p = 0.000). There is a significant relationship between the duration hypertension and event of hypertensive retinopathy in RSUD Dr. A. Dadi Tjokrodipo Bandar Lampung period 2017-2020